An additional replication origin causes cell cycle specific DNA replication fork speed - Skovgaard, Ole (Frontiers in Microbiology, 2025)
Replication fork speed (RFS) in Escherichia coli has long been considered constant throughout the replication and cell cycles. In wild-type cells, the circular chromosome is duplicated bidirectionally from oriC, yielding two replication forks that converge at the ter region. Under slow-growth conditions, cells are smaller at initiation than at termination, so DNA replication consumes a larger fraction of cellular resources early in the cell cycle. To challenge this paradigm, we analyzed an E. coli strain with an additional ectopic copy of oriC—designated oriX—inserted midway along the left replichore. In this mutant, replication initiates simultaneously from both oriC and oriX, resulting in four active replication forks early in the cycle. Specifically, the rightward-moving fork from oriX and the leftward-moving fork from oriC converge first, while the leftward-moving fork from oriX is halted at the terA site until the arrival of the rightward-moving oriC fork. Consequently, the number of active replication forks varies dynamically—from zero to four, then two, then one, and finally zero—compared to the fixed zero–two–zero pattern observed in wild-type cells. RFS was calculated using marker frequency analysis of deep sequencing data. Our analysis revealed that RFS is reduced by approximately one third when four replication forks are active and increases by about one fourth when only one fork is active, resulting in a 2-fold variation in RFS during the replication cycle. Moreover, delaying replication initiation or increasing the available dNTP pool normalized these variations, indicating that nucleotide supply is the primary constraint on replication speed. These findings demonstrate that RFS is not inherently constant within a replication cycle and provide a basis for further studies into the factors that regulate replication kinetics.